2019
DOI: 10.1002/sd.2000
|View full text |Cite
|
Sign up to set email alerts
|

Towards cross‐regional sustainable development: The nexus between information and communication technology, energy consumption, and CO2 emissions

Abstract: The environmental impact of information and communication technology (ICT) has drawn increasing attention for two decades. The behaviour of ICT is positive towards economic growth; however, its environmental implications cannot be ignored. This empirical research explores the roles of ICT, economic growth, and energy consumption in environmental pollution across different regions from 1990 to 2015. Robust long‐run panel data estimation methods fully modified ordinary least square and dynamic ordinary least squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(30 citation statements)
references
References 49 publications
0
30
0
Order By: Relevance
“…A major drawback in most of the empirical studies (e.g., Danish et al, 2019; Khan et al, 2019) in the literature is that these studies apply either OLS or FMOLS, both of which rely on the rigid assumption of cross‐sectional independence. To tackle this drawback, we opt for DSUR introduced by Mark et al (2005).…”
Section: Data and Econometric Methodologymentioning
confidence: 99%
“…A major drawback in most of the empirical studies (e.g., Danish et al, 2019; Khan et al, 2019) in the literature is that these studies apply either OLS or FMOLS, both of which rely on the rigid assumption of cross‐sectional independence. To tackle this drawback, we opt for DSUR introduced by Mark et al (2005).…”
Section: Data and Econometric Methodologymentioning
confidence: 99%
“…They revealed that tourist arrivals have a positive and statistically significant impact on the level of energy consumption and CO 2 emissions. According to Danish et al (2019), energy consumption is responsible for the increase in CO 2 emissions in all income groups. Liu et al (2019) studied for Pakistan covered the data peroid from 1980 to 2016.…”
Section: Empirical Literature Surveymentioning
confidence: 99%
“…Given these conflicting theories on the impact of ICTs on environmental quality, the literature on ICT emissions has also produced heterogeneous findings. For instance, some scholars maintain that ICTs improve environmental quality [25][26][27][28][29][30][31][32] while others document that ICT degrade the environment [33][34][35] .…”
Section: Introductionmentioning
confidence: 99%